PENGARUH PENGEMBANGAN KARIR TERHADAP PRODUKTIVITAS KARYAWAN PT POS INDONESIA (PERSERO) KENDARI - Rustam Supendy; Harsum Harsum (Mega Aktiva, 2018)
As for the formulation of the problem in this penelitisan Is career development has a significant influence on productivity Employees PT Pos Indonesia (PERSERO) Kendari. The purpose of this research is to know and analyze the influence of career development on employee productivity PT Pos Indonesia (PERSERO) Kendari. This research is a survey research with quantitative approach. The sample of this research is Employee Office of PT. Pos (Persero) Kendari City which amounted to 36 people with sampling technique saturated. Data were collected using questionnaire while data analysis used validity and realibility test as instrument test instrument, simple regression analysis, partial hypothesis test (t-test) was used to obtain accurate data to draw conclusion. Based on the research, the results obtained: that career development has a positive effect on work productivity. And it can be concluded that career development factors statistically affect the effort to improve worker productivity at the office of PT. Pos (Persero) Kendari City (p <0.05). Suggestion in this research It is better to maximize the existing performance in the work unit in need of increasing the role of human resource management by holding socialization and training on Human Resource Management about the role of the organization.